THE EFFECTIVENESS OF ANIMATION VIDEO IN IMPROVING STUDENTS’ LEARNING INTEREST AT SMP NEGERI 2 SUNGGUMINASA - Fuzia, Aldita Anggun; Muhayyang, Maemuna; Muhalim, Muhalim (Universitas Negeri Makassar, 2025)
This study aims to determine the effectiveness of using animation video to improve students' learning interests. The research method used was quantitative with a pre-experimental research design. The sample consists of 32 students from class IX.6, selected using a cluster random sampling technique. The data was collected using the questionnaire in the form of pre- and post-questionnaire as the research instrument. The data analysis results show that the use of animation video increased students' learning interest evidenced by the t-test value which is smaller than P (0.001 < 0.05) meaning that Ho is rejected, and Ha is accepted. So, it is concluded that the use of animation video is effective in improving students’ learning interests. Based on those results, it is considered that the use of animation video effectively gave significant results in the learning interest improvement among the students in class IX.6 at SMP Negeri 2 Sungguminasa.